Associations between functional capacity and work ability among elderly municipal employees. - Nygard, C. H.; Eskelinen, Leena; Suvanto, S.; Tuomi, Kaija; Ilmarinen, Juhani (Scandinavian Journal of Work, Environment & Health, 1991)
The relationship between objectively measured physical and mental functional capacity and work ability was studied among 137 workers with a mean age of 55 years. Of the physical capacity tests muscular strength correlated the best with the constructed work ability index. Cardiorespiratory capacity and work ability did not correlate statistically significantly. About 50% of the subjects was classified uniformly, and less than 10% not uniformly, with respect to muscular strength. The correlation between cardiorespiratory capacity and work ability was significant for those without, but not for those with, a musculoskeletal disease. The mental capacity tests had systematically lower correlations with work ability than the tests for physical capacity. The highest statistically significant correlation was found between visuomotor speed and work ability. Objective measurements of muscular strength seem useful for defining work ability, but other tests need to be improved to be more work-related. Furthermore, musculoskeletal diseases should be checked for when cardiorespiratory capacity is assessed.